2016
DOI: 10.1016/j.leukres.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TBK1 and IKKε, the non-canonical IκB kinases, as crucial pro-survival factors in HTLV-1-transformed T lymphocytes

Abstract: Persistent activation of NF-κB is a prerequisite for development of adult T cell leukemia-lymphoma (ATL) caused by human T cell leukemia virus type 1 (HTLV-1). HTLV-1 genome encodes a viral transforming protein named Tax, which constitutively activates the canonical IκB kinases (IKK), the central regulator of NF-κB signaling. However, the role of the non-canonical IκB kinases, TBK1 and IKKε, in the pathogenesis of HTLV-1-associated leukemia has not been evaluated. We here show that TBK1/IKKε are crucial pro-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…46,47 Immunotherapeutic targeting of Programmed death ligand −1 (PD-L1) can increase Th17 cell count, restoring IL-17A protein levels in naïve T-cells of patients with a loss-of-function STAT3 mutation. [46][47][48] Conversely, inducing Th17 cell differentiation by RORy agonist LYC-54143 simultaneously reduced PD-1 + cell numbers and PD-1 expression in vitro, and resulted in tumor growth inhibition in vivo in two murine models. 49 In ATL, PDL1 gene amplifications have been associated with worse prognosis, especially in aggressive subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Immunotherapeutic targeting of Programmed death ligand −1 (PD-L1) can increase Th17 cell count, restoring IL-17A protein levels in naïve T-cells of patients with a loss-of-function STAT3 mutation. [46][47][48] Conversely, inducing Th17 cell differentiation by RORy agonist LYC-54143 simultaneously reduced PD-1 + cell numbers and PD-1 expression in vitro, and resulted in tumor growth inhibition in vivo in two murine models. 49 In ATL, PDL1 gene amplifications have been associated with worse prognosis, especially in aggressive subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…42 Furthermore, recent studies have shown that NF-κB protects activated HSCs against TNFα-induced apoptosis, 43,44 and inhibition of NF-κB led to the promotion of HSC apoptosis, resulting in reduced severity of liver fibrosis. 42 Furthermore, recent studies have shown that NF-κB protects activated HSCs against TNFα-induced apoptosis, 43,44 and inhibition of NF-κB led to the promotion of HSC apoptosis, resulting in reduced severity of liver fibrosis.…”
Section: Anti-fibrotic Effects By Amlexanox Treatment On Hscs Are Pmentioning
confidence: 99%
“…Studies have suggested that inhibiting the transmembrane protein Programmed death ligand -1 (PD-L1) can increase Th17 cell count. Notably, human anti-PD-L1 antibodies restored IL-17A protein levels in naïve T-cells of patients with a loss-of-function STAT3 mutation [52][53][54] . Also noteworthy is the induction of Th17 cell differentiation by RORy agonist LYC-54143, which simultaneously reduced PD-1 + cell numbers and PD-1 expression in vitro, resulting in tumor growth inhibition in two murine models 55 .…”
Section: Discussionmentioning
confidence: 97%